Halal And Kosher Marketing Strategie - Fazryatul Hazrim Abd Rahim; Nor Aini Bt Muhammad; Faridah Hj. Hassan (Journal of Islamic Management Studies, 2017)
The purpose of this study is to understand the importance of food relating to Halal and Kosher. Several problems and issues were discussed. The research objectives are to identify the difference between Halal and Kosher products, to understand the Halal and Kosher today’s market and to understand how the certification for Halal and Kosher were executed. Marketing strategies were discussed in order to handle the demand for halal certification, challenges and strategies of Halal and Kosher’s food management. It was concluded that consumers need to put more pressure on the kosher and halal marketing system to use trademarked symbols that represent an organization that the consumer can hold accountable and which provides both the companies and the consumer with confidence in the kosher and/or halal status of the products being offered in the marketplace.